The female slave in Roman agriculture: changing the default - Roth, U. (2004)
This thesis deals with slaves. More precisely, it deals with the slave-run agricultural estates in Italy during the period of Roman imperial expansion. The main point to be addressed is that of the relationship between its two main genders: adult male and female agricultural slaves. Whilst scholarship has maintained for almost a century now that male slaves played a significantly more important role in this period than female slaves, this thesis will argue that their economic and social contributions were at least equal. It will further to this argue that the traditional view is largely based on a highly biased and discriminating attitude towards the role of women in the world of work, and on a more general disregard and subsequent unbalanced valuation of women's contributions.